Cohort study of the impact of direct acting antiviral therapy in patients with chronic hepatitis C and decompensated cirrhosis - Foster, Graham R.; Irving, William L.; Cheung, Michelle C.M.; Walker, Alex J.; Hudson, Benjamin E.; Verma, Suman; McLauchlan, John; Mutimer, David J.; Brown, Ashley; Gelson, William T.H.; MacDonald, Douglas C.; Agarwal, Kosh (Elsevier, 2016)
Background and Aims: All oral direct-acting antivirals (DAAs) effectively treat chronic hepatitis C virus (HCV) infection, but the benefits in advanced liver disease are unclear. We compared outcomes in treated and untreated patients with decompensated cirrhosis. Methods: Patients with HCV and decompensated cirrhosis or at risk of irreversible disease were treated in an Expanded Access Programme (EAP) in 2014. Treatment, by clinician choice, was with sofosbuvir, ledipasvir or daclatasvir, with or without ribavirin. For functional outcome comparison, untreated patients with HCV and decompensated cirrhosis who were registered on a database 6 months before treatment was available were retrospectively studied. Primary endpoint was sustained virological response 12 weeks post antiviral treatment (treated cohort) and the secondary endpoint (both cohorts) was adverse outcomes (worsening in MELD score or serious adverse event) within 6 months. Results: 467 patients received treatment (409 decompensated cirrhosis). Viral clearance was achieved in 381 patients (81.6%) – 209 from 231 (90.5%) with genotype 1 and 132 from 192 (68.8%) with genotype 3. MELD scores improved in treated patients (mean change -0.85) but worsened in untreated patients (mean + 0.75) (p<0.0001). Patients with initial serum albumin <35 g/l, aged >65 or with low (<135 mmol/L) baseline serum sodium concentrations were least likely to benefit from therapy. Conclusions: All oral DAAs effectively cured HCV in patients with advanced liver disease. Viral clearance was associated with improvement in liver function within 6 months compared to untreated patients. The longer term impact of HCV treatment in patients with decompensated cirrhosis remains to be determined.